From Music to Medicine: Transfer of Motor Skills from Piano Performance to Laparoscopic Surgery - Dimitrova, Valeria (Université d'Ottawa / University of Ottawa, 2021)
Background: Due to the deficit of knowledge on fine motor skill far transfer from one domain of expertise to another, piano performance and surgical training serve as a relevant, interdisciplinary context in which to study the transfer of motor skills given both have relatively well-established levels of performance and require complex fine motor skills. Musicians tend to demonstrate greater ease in all aspects of procedural knowledge which are known to contribute to the early stages of motor learning. Previous research in the Piano Pedagogy Research Laboratory (PPRL) found that extensive piano training was correlated with faster learning of surgical knot-tying skills. However, the short-term two-day timeline was a limitation of the study. Objective: Our project has built on previous work in the PPRL to address the short-term nature of previous studies by measuring a long-term performance curve as well as retention of surgical training and also expanded on the previous project by focussing this time on laparoscopic tasks. This study compared performance curves of two participant groups (pianists and controls) over five consecutive days and retention one week later, as measured by speed and accuracy of task completion. Laparoscopic training consisted of six tasks repeated at every session. Since laparoscopy involves a variety of abilities concurrently, we also administered a battery of ten psychometric tests to isolate and measure specific aspects of non-motor and fine motor skills. Results: There was no statistical difference between participant groups on the majority of laparoscopic training and psychomotor assessments based on two-way mixed ANOVA and Mann-Whitney U test analysis, respectively. There were also little to no significant correlations between abilities and laparoscopic performance. The only significant confounding variable was that the control group was significantly more interested in surgery than the musician group (p = .037). Conclusion: Overall, these results demonstrate that piano performance training did not far transfer to laparoscopic surgery. This is relevant to the debate on far transfer of motor skills given this study’s robust design which addressed previous shortcomings by including a longer timeline and more specifications of musicians’ characteristics. Our findings indicate that fine motor skills are domain specific to music and surgery, respectively.
Keywords: Motor learning; Skill transfer; Piano performance; Laparoscopic surgery; Fine motor skill; Psychometric tests; Visuospatial ability; Depth perception; Dexterity; Ambidexterity; Hand-eye coordination